Isolation and Diagnosis of Some Dermatophytes Using Nitrogen Base Tracking Technique (Scquence) - Saba kadhim Naser1, Meethaq Staar Abood2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A total of, 162 Samples of those infects with dermatophytes at lmam Hussein Teaching Hospital in Nasiryah city for the purpose of diagnosing some samples in a sequential manner , The samples included skin skimmers, nail clippers, hair pieces, Isolation and diagnosis of samples was carried out by conventional methods and then confirmed the diagnosis in a way that follows the nitrogen bases, where 10 samples were diagnosed and recorded in the gene bank , Trichophyton was the more frequent , than Epidermophyton ,A number of Candidia yeasts were also diagnosed in the traditional methods of appearance , It was a ratio of T. rubrum (28%) than T. interdigitale (24%), than T. mentagrophytes (21%), and also E. floccosum in the rate of (25%) , There are also ratios for the emergence of types of yeasts as a proportion C. albicans (32%) , Than C. parapsilosis (25%) , Than C. kruzi (22%) , and also C. dubllirensis in the rate of (19%) , Thes samples were collected from different ages and from both sexes .